Mapping the Three‐Dimensional Nanostructure of the Ionic Liquid–Solid Interface Using Atomic Force Microscopy and Molecular Dynamics Simulations. Issue 7 (25th January 2023) - Elbourne, Aaron; Dupont, Madeleine; Kariuki, Rashad; Meftahi, Nastaran; Daeneke, Torben; Greaves, Tamar L.; McConville, Christopher F.; Bryant, Gary; Bryant, Saffron J.; Besford, Quinn A.; Christofferson, Andrew J.
Abstract: Ionic liquids (ILs) are a widely investigated class of solvents for scientific and industrial applications due to their desirable and "tunable" properties. The IL–solid interface is a complex entity, and despite intensive investigation, its true nature remains elusive. The understanding of the IL–solid interface has evolved over the last decade from a simple 1D double layer, to a 2D ordered interface, and finally a liquid‐specific, complex 3D ordered liquid interface. However, most studies depend solely on one technique, which often only examine one aspect of the interfacial nanostructure. Here, a holistic study of the protic IL–solid interface is presented, which provides a more detailed picture of IL interfacial solvation. The 3D nanostructure of the ethylammonium nitrate (EAN)–mica interface is investigated using a combination of 1D, 2D, and 3D amplitude modulated‐atomic force microscopy and molecular dynamics simulations. Importantly, it is found that the EAN–mica interface is more complex than previously reported, possessing surface‐adsorbed, near‐surface, surface‐normal, and lateral heterogeneity, which propagates at relatively large distances from the solid substrate. The work presented in this study meaningfully enhances the understanding of the IL–solid interface. Abstract : The ionic liquid–solid interface is investigated using a combination of high‐resolution techniques. The 3D nanostructure of the ethylammonium nitrate (EAN)–mica interface is revealed using a combination of 1D, 2D, and 3D atomic force microscopy, molecular dynamics simulations, and theoretical calculations. Importantly, the EAN–mica interface is more complex than previously reported.